ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA KLUB SEPAKBOLA DI LIGA INGGRIS (Studi Kasus Pada Klub Sepakbola Arsenal, Chelsea dan Manchester United Periode Tahun 2012-2014) - B31108070, YO'OS SWARDI (Jurnal Manajemen Update, 2015)
Working capital is one aspect of company spending. If the company can not maintain a satisfactory level of working capital, then it is likely the company is unable to pay obligations that have matured. Analysis of the sources and uses of working capital is important for financial managers to determine how fund used and how to pay those needs. Especially for football club Arsenal, Chelsea and Manchester United would require the evaluation of sources and uses of working capital in order to achieve efficiency in the company. Purpose of this study to determine how the efficiency of resource management and use of working capital of Arsenal, Chelsea and Manchester United during the 2012-2014 period. This study use descriptive analysis. The results of this study indicate the source of policy implementation and the uses of working capital of Arsenal, Chelsea dan Manchester United during the period 2012-2014 has been less efficient in the sense of an reduction in working capital and in not accordance with the needs analysis and the use of working capital are planned. Therefore, it is expected to Arsenal , Chelsea and Manchester United the period 2015 can implement policies efficiently by improving sources of working capital for uses working capital the period of 2015. Keywords: source, using, working capital